2014
DOI: 10.1007/s00339-014-8655-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ductility, weakening of anisotropy behavior and local recrystallization in cold-rolled Ti-6Al-4V alloy strips by high-density electropulsing treatment

Abstract: The effect of high-density electropulsing treatment (EPT) on the microstructure, mechanical properties and fracture behavior of cold-rolled Ti-6Al-4V alloy strip was investigated. The results indicated that EPT accelerated the local recrystallization process tremendously in predeformed titanium alloy. The EPT-induced microstructural change resulted in remarkably increasing elongation to failure while remained tensile strength unchanged. In addition, anisotropy behavior of mechanical property is weakened dramat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Under high density pulse current, the differences of mechanical properties almost diminished at a maximum current density of 5.4 × 10 3 A·mm −2 [ 62 ]. Similar results were found in the Ti-6Al-4V alloy and showed that EPT weakened the anisotropy behaviour of materials during plastic deformation, which may be attracted to the formation of non-directional fine equiaxed grains; the selective effect of current also supplies the directional energy input for grains’ evolution to relieve mechanical properties’ anisotropy [ 101 ].…”
Section: Effects Of Ept On the Properties Of Materialssupporting
confidence: 59%
See 1 more Smart Citation
“…Under high density pulse current, the differences of mechanical properties almost diminished at a maximum current density of 5.4 × 10 3 A·mm −2 [ 62 ]. Similar results were found in the Ti-6Al-4V alloy and showed that EPT weakened the anisotropy behaviour of materials during plastic deformation, which may be attracted to the formation of non-directional fine equiaxed grains; the selective effect of current also supplies the directional energy input for grains’ evolution to relieve mechanical properties’ anisotropy [ 101 ].…”
Section: Effects Of Ept On the Properties Of Materialssupporting
confidence: 59%
“… The average maximum temperature of different metals and alloys with different peak current densities [ 24 , 30 , 52 , 53 , 59 , 63 , 67 , 78 , 82 , 85 , 98 , 101 , 112 , 114 , 123 , 125 , 131 ]. …”
Section: Figurementioning
confidence: 99%
“…Recently, a novel style of energy input assisted processing technology to process the materials aiming to improve the microstructure and toughness has emerged, that is high-energy electro-pulse treatment (EPT). Electro-plasticity, electric field, and electromagnetic field can be applied concurrently within a short time and lower temperature in this process with ultra-high efficiency and low-cost [8][9][10]. Gromov et al [11] studied the structure, phase composition and dislocation substructure of steel subjected to EPT and found the fatigue durability increases within short time treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, Jiang et al 15 accelerated the solid solution process of beta-Mg17Al12 into the alpha matrix with the help of EPT even in a very short time of several seconds. Our previous experiments [16][17][18][19][20][21][22][23] also successfully applied the EPT in processing predeformed titanium alloys lowering the processing temperature and persisting time with improving microstructure in recovery and recrystallization process, thus improving the mechanical properties of titanium alloy strips and obtained FGM in a single long strip material.…”
Section: Introductionmentioning
confidence: 97%